Outcomes After Laparoscopic Cholecystectomy in Hyperkinetic Biliary Dyskinesia. Issue 8 (August 2022) - Whitaker, Litton F.; Bosley, Maggie E.; Refugia, Justin M.; Powell, Myron S.; McNatt, Stephen S.; Westcott, Carl J.; Koch, Kenneth L.; Bennett, Paige; Rigdon, Joseph; Fernandez, Adolfo Z.
Background: Biliary dyskinesia (BD) is a poorly understood functional gallbladder disorder. Diagnosis is made with abdominal pain and an intact gallbladder without signs of anatomical obstruction on imaging or pathology. Our aim was to assess whether laparoscopic cholecystectomy (LC) resolves hyperkinetic BD symptoms. Methods: Records of patients ≥18 years of age, who underwent LC by four surgeons at a tertiary care center between 2012 and 2020, were retrospectively reviewed. Patients were excluded if they had a documented gallbladder ejection fraction (GBEF) <80% or had biliary stones or sludge on pathology or imaging. Demographic information, HIDA results, preoperative testing, operative details, gallbladder pathology, and symptom status at follow-up were collected from electronic medical records. Improvement in BD symptoms was assessed using McNemar's test. Risk differences with standard errors were employed to estimate percent reduction in symptoms. Results: Ninety-eight patients met inclusion criteria. Of those who presented for follow-up (n = 91), 92.3% (n = 84) reported partial or complete resolution of symptoms. Preoperative symptoms, including back pain (16.7%, 95% CI: [7.9%, 25.5%]; P < .0001), epigastric pain (31.1% [21.3%, 41.3%]; P < .0001), nausea (56.7% [45.0%, 65.8%]; P < .0001), RUQ pain (57.8% [46.1%, 66.9%]; P < .0001), and vomiting (27.8% [18.4%, 37.7%]; P < .0001) showed significant improvement after LC. Chronic cholecystitis and/or cholesterolosis were present on pathology in 79.8% of gallbladders. Discussion: Our study currently represents the largest cohort of patients with hyperkinetic BD. Laparoscopic cholecystectomy appears to result in resolution of symptoms for this clinical entity.